Factors Influencing High School Students’ Subject Choices in Relation to Class and Board of Study - Sahni, Kabir; Kothari, Roopam (JOURNAL OF INDIAN EDUCATION, 2023)
The purpose of this research is to evaluate the factors affecting subject choices according to the class and the board of study based on 8 factors, i.e., educational aspirations, practical application, enjoyment of the subject, scoring, self-motivation, teachers, parents and friends. The research is centered on a sample of 250 Indian high school students from three boards: Central Board of Secondary Education, International General Certificate of Secondary Education and International Baccalaureate Diploma Programme. Data was collected through a questionnaire and the questions were constructed using a 5-point Likert Scale. The study concluded that ‘English’ is the most preferred subject. Simultaneously, as we escalate towards higher classes, science is comparatively less popular, while economics and business studies become more popular. It was further found that while opting subjects, ‘educational aspiration’ was the primary reason amongst 9 and 10 graders. Whereas, ‘enjoyment’ outranked other reasons amongst 11 and 12 graders. In addition to it, ‘self-Motivation’ has the greatest impact in the majority of situations for the same. However, the effect of teachers and friends is relatively less significant. Lastly, we conclude that by enhancing student’s enjoyment, efficacy, grades and increasing subject’s value may lead to better subject choices and a better career choice.